2020
DOI: 10.1101/2020.11.19.390104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migraine Attacks as a Result of Hypothalamic Loss of Control

Abstract: To assess the natural trajectory of brain activity over the migraine cycle, we assessed (1) the cerebral perfusion and (2) the hypothalamic connectivity during spontaneous headache attacks with follow-up recordings towards the next migraine attack. Using pseudo-continuous arterial spin labelling and resting-state functional magnetic resonance imaging, 12 migraine patients were examined in 82 sessions. We detected cyclic changes of brain perfusion in the limbic circuit (insula, hippocampus, and nucleus accumben… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Moreover, the FC decrease between the SMN and VAN (posterior insula) observed by (Araújo et al, 2023) was not replicated, though other connections involving the SMN or VAN showed decreased FC in our case. Decreased FC within limbic structures and with the hypothalamus has also been observed (Stankewitz et al, 2021;Stankewitz & Schulz, 2022). Furthermore, M-post shows decreased FC bilaterally for connections involving SMN and VN, as well as left DAN and DMN, yet no differences were found in the existing literature.…”
Section: Fc Changes Across the Migraine Cycle (Across Menstrual Cycle...mentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, the FC decrease between the SMN and VAN (posterior insula) observed by (Araújo et al, 2023) was not replicated, though other connections involving the SMN or VAN showed decreased FC in our case. Decreased FC within limbic structures and with the hypothalamus has also been observed (Stankewitz et al, 2021;Stankewitz & Schulz, 2022). Furthermore, M-post shows decreased FC bilaterally for connections involving SMN and VN, as well as left DAN and DMN, yet no differences were found in the existing literature.…”
Section: Fc Changes Across the Migraine Cycle (Across Menstrual Cycle...mentioning
confidence: 69%
“…In a comprehensive review spanning fMRI studies from 2014 to 2021, only a small fraction (9 out of 114) included data partially collected during the ictal phase, and often the cycle phases were poorly defined (Schramm et al, 2023). Moreover, only 14 FC studies sampled more than one phase, and of these only 9 were longitudinal (Amin et al, 2018;Araújo et al, 2023;Filippi et al, 2022;Marciszewski et al, 2018;Meylakh et al, 2018;Schulte, Menz, et al, 2020;Schulte & May, 2016;Stankewitz et al, 2021;Stankewitz & Schulz, 2022), with some of them relying on the same sample and including 2 case studies. Furthermore, only 3 of the longitudinal studies sampled all migraine cycle phases and they did not compare them with healthy controls.…”
Section: Introductionmentioning
confidence: 99%